2012
DOI: 10.1111/j.1600-0536.2012.02114.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical antioxidants protect the skin from chemical‐induced irritation in the repetitive washing test: a placebo‐controlled, double‐blind study

Abstract: The superiority of the cream with antioxidants to the cream base suggests that reactive oxygen species, at least in part, play a role in the development of irritant contact dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…The best effect was achieved with the antioxidant containing cream, whereas the untreated skin showed the worst results. Other studies with creams containing antioxidants also showed positive skin effects with respect to contact allergies and contact dermatitis [67][68][69][70].…”
Section: Effect Of Topical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The best effect was achieved with the antioxidant containing cream, whereas the untreated skin showed the worst results. Other studies with creams containing antioxidants also showed positive skin effects with respect to contact allergies and contact dermatitis [67][68][69][70].…”
Section: Effect Of Topical Applicationmentioning
confidence: 99%
“…Schempp et al studied the effect of an antioxidant-containing cream, a base and barrier protection cream on untreated skin in order to analyze the hydration of the SC and the blood flow by a chemically induced contact dermatitis [67]. The best effect was achieved with the antioxidant containing cream, whereas the untreated skin showed the worst results.…”
Section: Effect Of Topical Applicationmentioning
confidence: 99%
“…On the other hand, application of vitamin E after SLS shortened the recovery time, as shown by its effects on TEWL, detached corneocytes, targetoid keratinocytes at the epidermis and at the dermis, and papillary shape irregularity reduction, as compared with the control site ( Fig. 4) (19). CONFOSCAN ® evaluation suggests that vitamin E prevents skin irritation and also stimulates repair mechanisms after irritating phenomena.…”
Section: Discussionmentioning
confidence: 94%
“…This positive effect of topical HA could be linked to its skin hydrating action [25] and skin barrier function improvement [26]. Topical HA could exert also anti-oxidant activity [27]. In addition, topical HA can modulate several skin cells functions: topical HA can have relevant effects on cell proliferation, recognition, and cell migration [28].…”
Section: Discussionmentioning
confidence: 99%